2011
DOI: 10.1007/s00066-011-2224-8
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Acute Radiodermatitis with an Oil-in-Water Emulsion Following Radiation Therapy for Breast Cancer

Abstract: Treatment of radiodermatitis with an oil-in-water emulsion was well tolerated, enhanced stratum corneum hydration, improved clinical indicators, and provided relief from itching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…Of the 47 studies, 22 studies adequately reported allocation concealment [31,32,35,37,39-41,43,45,47],[50-53,55,56,59,63,68,69,71],[72]. The method used to conceal the allocation sequence was not reported in the remaining studies, thus receiving a judgement of unclear risk of bias for this domain.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 47 studies, 22 studies adequately reported allocation concealment [31,32,35,37,39-41,43,45,47],[50-53,55,56,59,63,68,69,71],[72]. The method used to conceal the allocation sequence was not reported in the remaining studies, thus receiving a judgement of unclear risk of bias for this domain.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 lists the randomized studies on the prevention of acute radiation skin reactions in patients with breast cancer receiving radiotherapy in last 5 years. 4,[17][18][19][20][21][22][23][24][25][26][27][28] Randomized controlled studies have generated mostly negative results for use of skin care products in preventing or treating radiation dermatitis. Remarkably, patients receiving topical corticosteroids (mometasone furoate and betamethasone) during radiotherapy might experience reduced acute skin toxicity compared with placebo or moisturizing creams according to the result of three doubleblind studies with a larger population.…”
Section: Discussionmentioning
confidence: 99%
“…Acute effects begin with erythema, edema, pigment changes, and depilation. Even though, histological analyses of irradiated skin show hyperproliferation of the epidermis and thickening of the stratum corneum; transepiderml water loss (TEWL), a measure for skin barrier integrity, is significantly increased (Jensen et al ., 2011; Schmuth et al ., 2001). Severe radiation injury results in complete loss of the epidermis and persistent fibrinous exudates and edema.…”
Section: Current Understanding: Perception Of Radiation Skin Injurymentioning
confidence: 99%
“… * Data compiled from (Elliott et al ., 2006; Holler et al ., 2009; Jensen et al ., 2011; Okunieff et al ., 2006; Pommier et al ., 2004; Ryan et al ., 2011; Xiao et al ., 2006) …”
Section: Figurementioning
confidence: 99%